Tumor-targeting biomimetic sonosensitizer-conjugated iron oxide nanocatalysts for combinational chemodynamic–sonodynamic therapy of colorectal cancer. Issue 24 (1st June 2022) - Chen, Xiaodan; Cheng, Danling; Ding, Mengbin; Yu, Ningyue; Liu, Jiansheng; Li, Jingchao; Lin, Lin
Abstract : Tumor-targeting biomimetic sonosensitizer-conjugated iron oxide nanocatalysts are developed for combinational chemodynamic–sonodynamic therapy of colorectal cancer. Abstract : Nanoparticle-based tumor therapy strategies have been widely developed, while the therapeutic efficacy is often limited due to poor accumulation of nanoparticles in tumor tissues and low antitumor effect of sole therapeutic modality. In this study, we report the construction of tumor-targeting biomimetic sonosensitizer-conjugated iron oxide (Fe3 O4 ) nanocatalysts to mediate combinational action of chemodynamic therapy (CDT) and sonodynamic therapy (SDT) for the treatment of colorectal cancer. Bovine serum albumin (BSA)-modified Fe3 O4 nanoparticles were synthesized using a basic co-precipitation method, and were conjugated with chlorin e6 (Ce6) as the sonosensitizers, followed by surface camouflage of a CT26 cancer cell membrane to construct the tumor-targeting biomimetic nanocatalysts (MBFC). The obtained MBFC nanocatalysts could present a strong catalysis ability and efficient sonodynamic property to generate an abundant amount of reactive oxygen species (ROS) under ultrasound (US) treatment in the tumor microenvironment. Cellular internalization experiments verified the high cellular uptake efficacy of MBFC due to the cell membrane-mediated homologous targeting mechanism. The MBFC nanocatalysts enabled the combinational action of CDT and SDT, and could markedly induce the apoptosis of CT26 cells in vitro and greatly inhibit the growth of CT26 tumors in living mice. This study thus provides a tumor-targeting biomimetic nanoplatform for the effective therapy of tumors.